Pv Powered Electronic Circuits Designed to Decrease Road Accidents - Şenpınar, Ahmet (My University, 2017)
One way of the utilizing solar energy is to use pv panel which generates electricity energy as expose to the solar radiation on it. Pvpanels are utilized1 in many areas such as lighting and stand-alone systems, the grid connected systems, pv power plants, satellite,space, communications..etc. Especially in today's green areas and parks, they are used for lighting and irrigation. The usage of pvpanels on the roads is a different usage aim of renewable energy sources. Some of them in highways are as follows: the lighting onmotorways, traffic signaling, routing sheets, bridges and viaducts lighting, the needed energy of petrol stations, the charger unit ofhybrid vehicles, and the determination of car numbers on the road. An electronic circuit design can be placed onto the highways. Withthe help of electronic sensors in electronics circuit placed on the road is to aim for reducing traffic accidents. It was particularly sharpbend and the angle where very tight, sending a place of warning signal in the lane against the emergence or ramp into the corner withthe help of designing electronic circuits on the road if you have a vehicle coming in the opposite direction to help the driver. As aresult, it prevents damage to that or give incorrect overtaking a vehicle enters the opposite direction.
Keywords: Mühendislik; Elektrik ve Elektronik; Enerji ve Yakıtlar; Taşınım Bilimi ve Teknolojisi